EVALUASI GENERATOR TENAGA SURYA PORTABEL UNTUK DUKUNGAN LISTRIK KAPAL NELAYAN TRADISIONAL - Rizqi Ilmal Yaqin; Bobby Demeainto; Tegar Lagsmana; Mega Lazuardi Umar (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
This paper presents the model and performance of a portable solar power generation system designed specifically for the electricity needs of fishermen. The objective of this study is to evaluate the performance of the portable solar generator under various environmental conditions. The outline of this paper includes the design process, fabrication, and testing conducted under three different weather conditions. The main components of the system consist of photovoltaic (PV) modules, enclosures, batteries, solar charge controllers, inverters, and other supporting components. The three weather conditions examined during testing are uncertain bright rain, clear bright conditions, and heavy rain. The assessment focuses on environmental parameters, power output, and the efficiency of the portable solar generator. The results indicate that weather conditions significantly impact environmental factors such as solar radiation and ambient temperature, which are essential for effective natural cooling of module. The maximum output power of this solar panel generator system is 60,05 watts, with an efficiency of 13%. This system is designed to meet the operational needs of fishermen, with a portable design that facilitates their activities.